Technology Empowerment in Learning: Student Perspective Study on Virtual Laboratory to Support Independent Learning in Independent Campus - Setiawan, Wawan; ., Sugianto; ., Riandi; Prasetyo, Yogi (KnE Social Sciences, 2024)
Virtual laboratory is one of the solutions that can be used for practical or experimental activities in the context of independent learning on an independent campus, which is carried out outside the laboratory, especially during the Covid-19 pandemic. However, in practice, there are several obstacles so the use of virtual laboratories has not been massive. This study aims to analyze the student’s perspective on the virtual laboratory in forcing conditions during the Covid-19 pandemic. The research method uses a survey with a questionnaire technique to capture the perspectives of students of the Biology Education Study Program at one of the universities in West Java. The perspectives studied include innovation, urgency, usefulness, and motivation which are grouped into positive and negative perspectives. The results showed that most of the students had a positive perspective on the virtual laboratory by 81.64%, and a negative perspective of 18.36%. Among the four indicators, motivation is the smallest positive perspective although it is larger than the negative perspective. This research can give the conclusion that the virtual laboratory needs to be continuously developed along with the improvement of students’ technological skills or literacy. Keywords: technology empowerment, student perspective study, virtual laboratory, independent learning